An Analysis of Figurative Language Used in Noor Unnahar's Poems - Shalva Sakinah Siahaan; Eni Rosnija; Urai Salam (Universitas Islam Negeri Palopo, 2025)
This research aims to find out the kinds of figurative language used in Noor Unnahar’s poems, the meaning of figurative language, and the dominant kind of figurative language used in Noor Unnahar’s poems. This research is qualitative research with the data collection technique using document or content analysis. The data were obtained from Noor Unnahar’s poems book entitled “Yesterday I was the Moon. The findings of this research show that there are eight kinds of figurative language used in Noor Unnahar’s poem. They are metaphor, personification, simile, symbol, hyperbole, metonymy, paradox, and allegory. There are 116 sentences that contain figurative language. Out of 116 sentences, there are 36 items or 31% of metaphor, 33 items or 28% of personification, 21 items or 18% of simile, 9 items or 8% of symbol, 7 items or 6% of hyperbole, 5 items or 4% of metonymy, 4 items or 3% of paradox, and 1 item or 1% of allegory. Thus, it can be indicated that the dominant kind of figurative language used in the poems is metaphor.